Utilização da sísmica de reflexão rasa no estudo da morfodinâmica de rios na região amazônica - FURTADO, Camila da Cunha (Universidade Federal do Pará, 2019)
The main idea of this research is identify and characterize morphodynamic phenomena present on the lay of the Pará river and foz of the Tocantins river, this area comprises from the Bocas bay unto east portion of the Marajó island. It is a region where exists scarcity of information and data about constitution and morphology of the lay, there is necessity to search new knowledge. Sediment samples from the bottom of the river were collected with the assistance of a Van Veen sampler, 181 (one hundred eighty-one) samples submitted to macroscopic analysis aiming to identify the type of material which composes the bottom. With the data of hydrodynamic modeled assistance was possible to connect the patterns of bottom forms with the sort of sediment which composes the lay and the prevailing hydrodynamic in the local. Based on the seismic data, was possible to identify and map the sonographic patterns in 15 types of echoes, classified in four categories. The less frequent echo types are the ones which present very irregular lays and little or no acoustic signal penetration. Specially the C1 type characterized by diffraction hyperbolas presence and the D1 type which treat responses arising from large deposits of sediments, found just in two forms of acoustic. The most significant bottom forms were identified on the stretch where the Canaticu river flows to Pará river where the principal canal width decreases from 8km to 4km in upper depth to 20m. The adhibition geophysical methods (acoustics), by the use of the Sub-Bottom profiler SB-0512, enable the knowing of the bottom forms, as well as its dimensions that those submerged forms show over the studied region. The way how this region’s lay sets itself and the dimensions that those corps reach can affect the sailing on some river’s stretch, as well as it can affect future civilian building. Therefore, this work opens ways to future more appropriate investigations on the issues mentioned above.